PHYTOTHERAPEUTIC TREATMENT OF ALLERGIC RHINITIS IN AUTISTIC SUBJECT - Lydia Ferrara; Daniele Naviglio; Arturo Armone Caruso (European Scientific Journal, ESJ, 2014)
In this study the efficacy of a nasal spray based on extract of lemon pulp for treatment of allergic rhinitis in autistic subjects by nasal cytology was evaluated. The extract of lemon pulp was obtained by means of an innovative technology of solid-liquid extraction using Extractor Naviglio or Rapid Solid-Liquid Dynamic Extractor, that can extracts vegetable matrices of each species, by using different types of solvents (organic and/or inorganic liquids). Due to pressure-depressure action, by using water as extractive liquid it is possible to extract both hydrophilic and lipophilic substances contained in vegetables. The efficacy of the lemon based nasal spray has been tested on 20 young patients aged between three and eight years (10 males and 10 females, mean age 5.5 years). The cytology was performed by exfoliative technique, with a sterile swab soaked in sterile saline solution and then crawled on the middle part of the inferior turbinate. The collected sample was stained with the method of May-Giemsa Grumwald to highlight the morphological changes of the nasal epithelium before and after therapy based on nasal spray. Experimental data demonstrated that the antiinflammatory effect of the lemon based nasal spray was a safe medical device as an aid in the reduction of inflammatory cells observed on rinocitogram. The lemon based nasal spray containing extract of lemon pulp can be used in all autistic patients, even in children, given the absence of alcohol.